Multiscale Memory Autoencoder and Spatial Filtering for Hyperspectral Anomaly Detection - Ma, Ziyang; Zhang, Yongshan; Lian, Yuyun; Jiang, Xinwei; Liu, Xiaobo; Cai, Zhihua (IEEE geoscience and remote sensing letters, 2025)
The hyperspectral anomaly detection (HAD) aims to identify potential anomalies from complex backgrounds. Most reconstruction-based autoencoders equally treat background pixels and anomalies or ignore potential spatial information. In this letter, we propose an HAD method based on multiscale memory autoencoder and spatial filtering, abbreviated as SFM2AE. Specifically, by introducing memory modules into different hidden layers of the autoencoder, multiscale reconstruction of background and anomaly pixels is achieved in the spectral domain. In addition, morphological filtering in the spatial domain is used to extract spatial structural information from anomalies. Joint spatial-spectral anomaly detection is achieved by combining multiscale memory autoencoder and spatial filtering. Experiments demonstrate superior detection performance of the proposed method over the state-of-the-art methods.